Peran Kepemimpinan Transformasional dan Kompetensi Profesional Guru Terhadap Hasil Belajar Siswa Sekolah Dasar di SDN Se Kecamatan Serang: Peran Kepemimpinan Transformasional dan Kompetensi Profesional Guru Terhadap Hasil Belajar Siswa Sekolah Dasar di SDN Se Kecamatan Serang - Dhea Fujha Raniayu; Mutoharoh; Andriani Sariwardini (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the influence of transformational leadership and teachers' professional competence on the learning outcomes of elementary school students in public elementary schools (SDN) across the Serang District. The research method used is descriptive quantitative. The sample in this study consists of teachers and students from several public elementary schools in the Serang District. The research instruments include questionnaires and documentation of students' learning outcomes. The data were analyzed using multiple linear regression. The results of the study indicate that both the school principals' transformational leadership and the teachers' professional competence have a significant and positive effect on students' learning outcomes. This study highlights the importance of improving the quality of leadership and teachers' professional competence in efforts to enhance the quality of education in elementary schools.